author Chung-chieh Shan Fri, 10 Jun 2011 00:04:51 +0000 (02:04 +0200) committer Chung-chieh Shan Fri, 10 Jun 2011 00:04:51 +0000 (02:04 +0200)
 cps.mdwn patch | blob | history

index bb478c6..35d0680 100644 (file)
--- a/cps.mdwn
+++ b/cps.mdwn
@@ -71,30 +71,30 @@ beta reduction: beta reduction does not occur underneath a lambda.
That is, `(\x.y)z` reduces to `z`, but `\w.(\x.y)z` does not, because
the `\w` protects the redex in the body from reduction.
(A redex is a subform ...(\xM)N..., i.e., something that can be the
-target of beta reduction.)
+target of reduction.)

Start with a simple form that has two different reduction paths:

reducing the leftmost lambda first: `(\x.y)((\x.z)w)  ~~> y`

-reducing the rightmost lambda first: `(\x.y)((\x.z)w)  ~~> (x.y)z ~~> y`
+reducing the rightmost lambda first: `(\x.y)((\x.z)w)  ~~> (\x.y)z ~~> y`

After using the following call-by-name CPS transform---and assuming
that we never evaluate redexes protected by a lambda---only the first
reduction path will be available: we will have gained control over the
order in which beta reductions are allowed to be performed.

-Here's the CPS transform:
+Here's the CPS transform defined:

-    [x] => x
-    [\xM] => \k.k(\x[M])
-    [MN] => \k.[M](\m.m[N]k)
+    [x] = x
+    [\xM] = \k.k(\x[M])
+    [MN] = \k.[M](\m.m[N]k)

Here's the result of applying the transform to our problem term:

-    [(\x.y)((\x.z)w)]
-    \k.[\x.y](\m.m[(\x.z)w]k)
-    \k.(\k.k(\x.[y]))(\m.m(\k.[\x.z](\m.m[w]k))k)
+    [(\x.y)((\x.z)w)] =
+    \k.[\x.y](\m.m[(\x.z)w]k) =
+    \k.(\k.k(\x.[y]))(\m.m(\k.[\x.z](\m.m[w]k))k) =
\k.(\k.k(\x.y))(\m.m(\k.(\k.k(\x.z))(\m.mwk))k)

Because the initial `\k` protects the entire transformed term,
@@ -102,11 +102,14 @@ we can't perform any reductions.  In order to see the computation
unfold, we have to apply the transformed term to a trivial
continuation, usually the identity function `I = \x.x`.

-    [(\x.y)((\x.z)w)] I
-    \k.[\x.y](\m.m[(\x.z)w]k) I
-    [\x.y](\m.m[(\x.z)w] I)
+    [(\x.y)((\x.z)w)] I =
+    (\k.[\x.y](\m.m[(\x.z)w]k)) I
+     *
+    [\x.y](\m.m[(\x.z)w] I) =
(\k.k(\x.y))(\m.m[(\x.z)w] I)
+     *           *
(\x.y)[(\x.z)w] I
+     *
y I

The application to `I` unlocks the leftmost functor.  Because that
@@ -115,28 +118,37 @@ CPS transform of the argument.

Compare with a call-by-value xform:

-    {x} => \k.kx
-    {\aM} => \k.k(\a{M})
-    {MN} => \k.{M}(\m.{N}(\n.mnk))
+    {x} = \k.kx
+    {\aM} = \k.k(\a{M})
+    {MN} = \k.{M}(\m.{N}(\n.mnk))

This time the reduction unfolds in a different manner:

-    {(\x.y)((\x.z)w)} I
+    {(\x.y)((\x.z)w)} I =
(\k.{\x.y}(\m.{(\x.z)w}(\n.mnk))) I
-    {\x.y}(\m.{(\x.z)w}(\n.mnI))
+     *
+    {\x.y}(\m.{(\x.z)w}(\n.mnI)) =
(\k.k(\x.{y}))(\m.{(\x.z)w}(\n.mnI))
-    {(\x.z)w}(\n.(\x.{y})nI)
+     *             *
+    {(\x.z)w}(\n.(\x.{y})nI) =
(\k.{\x.z}(\m.{w}(\n.mnk)))(\n.(\x.{y})nI)
-    {\x.z}(\m.{w}(\n.mn(\n.(\x.{y})nI)))
+     *
+    {\x.z}(\m.{w}(\n.mn(\n.(\x.{y})nI))) =
(\k.k(\x.{z}))(\m.{w}(\n.mn(\n.(\x.{y})nI)))
-    {w}(\n.(\x.{z})n(\n.(\x.{y})nI))
+     *             *
+    {w}(\n.(\x.{z})n(\n.(\x.{y})nI)) =
(\k.kw)(\n.(\x.{z})n(\n.(\x.{y})nI))
+     *      *
(\x.{z})w(\n.(\x.{y})nI)
-    {z}(\n.(\x.{y})nI)
+     *
+    {z}(\n.(\x.{y})nI) =
(\k.kz)(\n.(\x.{y})nI)
+     *      *
(\x.{y})zI
-    {y}I
+     *
+    {y}I =
(\k.ky)I
+     *
I y

Both xforms make the following guarantee: as long as redexes
@@ -144,7 +156,7 @@ underneath a lambda are never evaluated, there will be at most one
reduction available at any step in the evaluation.
That is, all choice is removed from the evaluation process.

-Questions and excercises:
+Questions and exercises:

1. Why is the CBN xform for variables `[x] = x' instead of something
involving kappas?
@@ -177,22 +189,22 @@ well-typed.  But what will the type of the transformed term be?

The transformed terms all have the form `\k.blah`.  The rule for the
CBN xform of a variable appears to be an exception, but instead of
-writing `[x] => x`, we can write `[x] => \k.xk`, which is
+writing `[x] = x`, we can write `[x] = \k.xk`, which is
eta-equivalent.  The `k`'s are continuations: functions from something
to a result.  Let's use &sigma; as the result type.  The each `k` in
the transform will be a function of type &rho; --> &sigma; for some
choice of &rho;.

We'll need an ancilliary function ': for any ground type a, a' = a;
-for functional types a->b, (a->b)' = a' -> (b' -> o) -> o.
+for functional types a->b, (a->b)' = ((a' -> o) -> o) -> (b' -> o) -> o.

Call by name transform

Terms                            Types

-    [x] => \k.xk                     [a] => (a'->o)->o
-    [\xM] => \k.k(\x[M])             [a->b] => ((a->b)'->o)->o
-    [MN] => \k.[M](\m.m[N]k)         [b] => (b'->o)->o
+    [x] = \k.xk                      [a] = (a'->o)->o
+    [\xM] = \k.k(\x[M])              [a->b] = ((a->b)'->o)->o
+    [MN] = \k.[M](\m.m[N]k)          [b] = (b'->o)->o

Remember that types associate to the right.  Let's work through the
application xform and make sure the types are consistent.  We'll have
@@ -202,11 +214,11 @@ the following types:
N:a
MN:b
k:b'->o
-    [N]:a'
-    m:a'->(b'->o)->o
+    [N]:(a'->o)->o
+    m:((a'->o)->o)->(b'->o)->o
m[N]:(b'->o)->o
m[N]k:o
-    [M]:((a->b)'->o)->o = ((a'->(b'->o)->o)->o)->o
+    [M]:((a->b)'->o)->o = ((((a'->o)->o)->(b'->o)->o)->o)->o
[M](\m.m[N]k):o
[MN]:(b'->o)->o